Social and Economic Vulnerability in The Sub-Watershed of Karang Mumus, East Kalimantan Province - Sri Endayani; Ronggo Sadono; Ambar Kusumandari; Hartono Hartono (Institut Pertanian Bogor (IPB University), 2019)
Changes in land use influence the social and economic characteristics as well as the environmental problems in a sub-watershed. To support the management of a sub-watershed, land use scenarios (biophysics) must be prepared and community involvement level must be improved. So far, the factors used for monitoring and evaluating sub-watershed performance have not been used thoroughly. This research is aimed at finding out the social and economic vulnerabilities tied to the monitoring and evaluation of sub-watershed performance across the sub-districts. This research uses quantitative methods employed to process primary data (biotic: vegetation and settlement, and abiotic: land, climate, geomorphology, and geology), secondary data (community data sourced from the data of BPS; Central Bureau of Statistics) of East Kalimantan Province; in September 2017), and socio-economic data (direct interviews using questionnaires). The primary data were obtained after processing map interpretation and from observation. The results show that high socio-economic vulnerability occurs in areas of high land use vulnerability. Sub-watershed management will be successful if it is done through a